Biogenic silica cycling in the Skagerrak - Spiegel, Timo; Dale, Andrew W.; Lenz, Nina; Schmidt, Mark; Sommer, Stefan; Kalapurakkal, Habeeb Thanveer; Przibilla, Anna; Lindhorst, Sebastian; Wallmann, Klaus (Frontiers in Marine Science, 2023)
Dissolved silicate (H4SiO4) is essential for the formation of the opaline skeletal structures of diatoms and other siliceous plankton. A fraction of particulate biogenic silica (bSi) formed in surface waters sinks to the seabed, where it either dissolves and returns to the water column or is permanently buried. Global silica budgets are still poorly constrained since data on benthic bSi cycling are lacking, especially on continental margins. This study describes benthic bSi cycling in the Skagerrak, a sedimentary depocenter for particles from the North Sea. Biogenic silica burial fluxes, benthic H4SiO4 fluxes to the water column and bSi burial efficiencies are reported for nine stations by evaluating data from in-situ benthic landers and sediment cores with a diagenetic reaction-transport model. The model simulates bSi contents and H4SiO4 concentrations at all sites using a novel power law to describe bSi dissolution kinetics with a small number of adjustable parameters. Our results show that, on average, 1100 mmol m-2 yr-1 of bSi rains down to the Skagerrak basin seafloor, of which 50% is released back to overlying waters, with the remainder being buried. Biogenic silica cycling in the Skagerrak is generally consistent with previously reported global trends, showing higher Si fluxes and burial efficiencies than deep-sea sites and similar values compared to other continental margins. A significant finding of this work is a molar bSi-to-organic carbon burial ratio of 0.22 in Skagerrak sediments, which is distinctively lower compared to other continental margins. We suggest that the continuous dissolution of bSi in suspended sediments transported over long distances from the North Sea leads to the apparent decoupling between bSi and organic carbon in Skagerrak sediments.